Ecstatic Encounters Bahian Candomblé and the Quest for the Really Real - van de Port, Mattijs (Amsterdam University Press, 2011)
Ecstatic Encounters takes its readers to the threshold of Candomblé temples in Bahia, Brazil, where - for many generations -- members of this spirit-possession cult and curious outsiders have been meeting to marvel at each other's otherness. Having allowed himself to be baffled by Candomblé's mysteries and miracle productions, the author explores the notion of 'the-rest-of-what-is': the excess that is the inevitable by-product of all reality definitions; the non-sensical that is the surplus of all culturally informed sense-making. Ethnographical insights in Afro-Brazilian mysticism are thus made to speak to anthropological forms of world-making, in a study that rejects the totalizing pretensions of all reality definitions, emphatically including those of academia. The theoretical importance of this book lies in its critical assessment of the constructivist paradigm that long dominates cultural and social anthropology. Adopting the Lacanian premise that the meaningful worlds we inhabit are lacking, and depend on fantasy and make-belief to be perceived as coherent, persuasive and incontestable, this study argues that the analysis of cultural forms should always include an exploration of the processes of cultural enchantment that endow man-made worlds of meaning with a sense of the really real. Ecstatic Encounters is written in an accessible, engaging, literary style. Philosophical issues are taken out on the streets, to be pondered in the face of everyday life; just as mundane dimensions of being are allowed to soil the conventional proprieties of academic text production.